(untitled) (Indian Journal of Animal Production and Management, 2024)
An experiment was conducted to compare the performance of Khaki Campbell and Maithili ducks under extensive system of management in middle gangetic plain (MGP) of Bihar where small water bodies are available. Brooding of ducklings for one month was managed with commercial feed after which they were exposed to free range management system. Leftover feed material and kitchen wastes were provided and vaccination against duck plague was done in subsequent period. Growth and production performances, mortality and egg quality data were recorded. The study revealed that Khaki Campbell ducks gained significant body weight as compare to Maithili duck from day old to 24th week of age due to variation in genotype. Attainment of early sexual maturity with significantly more egg production up to 40th week was observed in Khaki Campbell whereas egg weight and other egg traits were better in native ducks. Egg production rate of local native ducks (21.46 %) was found significantly lower (P<0.001) compared to Khaki Campbell duck (32.05%). The age at sexual maturity (female) of different genotypes of ducks were 178.92 (Khaki Campbell) and 191.12 (native ducks) days which differed significantly (P<0.05). Maithili ducks laid eggs of thinner shell (0.41mm). The mortality rate in local duck was significantly lower (P<0.05) compared to Khaki Campbell ducks. Economics of duck rearing between the varieties revealed a non-significant difference signifying that both Khaki Campbell and native ducks are suitable under extensive system of management.